NEURODEGENERATIVE AND NEUROINFLAMMATORY DISARRAYS IN PROGENIES AND ADULTS - MOHANAPRIYA CHELLADURAI,; SANGEETHA DAMODARAN,; RENGARAJ SAHASRANAM,; VAISHNAVI DEVI SRINIVASAN,; KARTHIKEYAN VIJAYAN,; GOPINATH MARGAVELU., (International Journal of Pharma and Bio Sciences, 2015)
Neurodegenerative disorders of childhood encompass a large, heterogeneous group of diseases that result from specific genetic and biochemical defects, chronic viral infections, and varied unknown causes. Progenies with suspected neurodegenerative disorders were once subjected to brain and neural biopsies, but with modern neuroimaging techniques and specific biochemical and molecular diagnostic tests, these invasive procedures are rarely necessary. The hallmark of a neurodegenerative disease is regressionandprogressivedeteriorationof neurologic function with loss of speech, vision, hearing, or locomotion, often associated with seizures, feeding difficulties, and impairment of intellect.Neuroinflammation is yet another neuronal disorder which is the inflammatory responses in acute damages and disorders necessary for homeostatic and defensive mechanisms of repair, regeneration and healing, chronic inflammatory signals in low-grade magnitude promote the development of a host of disorders ranging from cancer, diabetes, hypertension and cardiovascular disorders (CVDs). In total, the current review focuses our knowledge in the field of factors influencing inflammation and the mechanisms of metabolic dysfunctions. Also, anti-inflammatory therapies for chronic diseases have been successful to some extent. The effects of metabolic inflammation due to chronic factors is not just circumscribed to the peripheral metabolic tissues as was believed earlier, but is etiologically important for the CNS and especially the hypothalamus which drives central dysregulation of metabolic homeostasis.